2017
DOI: 10.1093/tropej/fmx084
|View full text |Cite
|
Sign up to set email alerts
|

Change in Pneumococcus Serotypes but not Mortality or Morbidity in Pre- and Post-13-Valent Polysaccharide Conjugate Vaccine Era: Epidemiology in a Pediatric Intensive Care Unit over 10 Years

Abstract: SPD is associated with significant morbidity and mortality, despite treatment with systemic antibiotics and ICU support. The expanded coverage of 13-valent PCV results in the reduction of Serotypes 6 and 19 but not mortality/morbidity associated with SPD in the setting of a PICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Our findings indicated that S. pneumoniae serotype 19A is dominant in Korea, and serotype 3 is currently dominant in Hong Kong, despite these serotypes being included in PCV13. These results are in agreement with recent epidemiological studies from both and Hong Kong 8 , 17 , 18 and Korea. 13 A survey of incidence rates in Hong Kong from 1995 to 2017 found that IPD cases due to serotype 3 were steadily increasing across all vaccine eras.17 Consistent with this, several studies have demonstrated a lack of PCV13 effective ness against IPD caused by serotype 3,40 and studies from the United States and the United Kingdom have highlighted the persistence of serotype 3 after PCV13 introduction.41,42 Regarding serotype 19A, Data from 2010–2015 in Korea showed that, although serotype 19A prevalence decreased steadily, it remained as prevalent as many non-PCV serotypes in 2015 and was the most prevalent serotype overall during this time period.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings indicated that S. pneumoniae serotype 19A is dominant in Korea, and serotype 3 is currently dominant in Hong Kong, despite these serotypes being included in PCV13. These results are in agreement with recent epidemiological studies from both and Hong Kong 8 , 17 , 18 and Korea. 13 A survey of incidence rates in Hong Kong from 1995 to 2017 found that IPD cases due to serotype 3 were steadily increasing across all vaccine eras.17 Consistent with this, several studies have demonstrated a lack of PCV13 effective ness against IPD caused by serotype 3,40 and studies from the United States and the United Kingdom have highlighted the persistence of serotype 3 after PCV13 introduction.41,42 Regarding serotype 19A, Data from 2010–2015 in Korea showed that, although serotype 19A prevalence decreased steadily, it remained as prevalent as many non-PCV serotypes in 2015 and was the most prevalent serotype overall during this time period.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, although serotypes 22F and 33F are two of the most commonly observed non-PCV13 serotypes in children with IPD, 16 we observed only a minimal burden from these serotypes in the current analysis. This is likely because these serotypes were rarely or never observed in most serotyping studies from Korea and Hong Kong, 8 , 12 , 13 , 17 , 49 , 50 suggesting a geographically tailored approach to surveillance, vaccination policy, and vaccine development will be needed. However, even in locations where serotypes 22F and 33F are rare, their invasiveness, which is comparable to that of serotype 19A, 51 may prioritize them for targeting by new PCVs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, severe IPD caused by serotype 3 remains prevalent especially in PICU setting despite its reputed coverage by PCV 13. 1 The phenomenon of the persistence of serotype 3 has also been also observed globally. 2 Pneumococcal-associated HUS appears to be a known complication only with serotype 3 IPD.…”
Section: Serotype 3 Pneumococcal-associated Hemolytic Uremic Syndrome...mentioning
confidence: 91%